Conflicting claims over income distribution and financial dollarisation in Argentina - Fabián Amico (Cuadernos de Economía)
From a long-term perspective, and based on a political economy approach, the article presents the complex interaction between the distributional conflict, the different roles of the exchange rate and persistent capital outflows. This articulation occurred throughout the cycle of Peronist governments (2003-2015) and subsequently became even more complex with the unsustainable increase in external debt and the attempts at neoliberal restoration.